Alexithymia and Its Associations With Depression, Suicidality, and Aggression: An Overview of the Literature - Hemming, Laura; Haddock, Gillian; Shaw, Jennifer; Pratt, Daniel (Frontiers in Psychiatry, 2019)
Depression affects around 4 to 10% of the general population in England. Depression can often lead to behaviours and thoughts related to suicide and aggression, which have a social and economic burden to the United Kingdom. One construct that has been theorised as having an association with these behaviours is alexithymia. People with alexithymia have difficulties identifying and describing their emotional experiences. To date, there is no consensus on types or causes of alexithymia. Whilst the literature evidences a strong relationship between alexithymia and suicidality and aggression, little is known about the nature of this relationship. The present article will attempt to describe the extant literature on this relationship, drawing out some of the contentions and unanswered questions.